Extraction, Characterization and Evaluation of Orange Peel Waste Derived Pectin as a Pharmaceutical Excipient - Srivastava, Pranati; Malviya, Rishabha (Natural Products Journal, The, 2011)
Objective: The objective of the present work was extraction of pectin from industrial waste of orange fruit peel and further characterization as pharmaceutical excipient. Study includes phytochemical screening, micromeritic properties, flow behavior and to find out the surface tension, viscosity and swelling index of extracted pectin. The work also emphasizes to evaluate the disintegrating properties of extracted pectin in solid dosage form. Methods: Orange peel pectin was obtained using acidified water based extraction in soxhlet apparatus. Pharmacopoeial procedures were used to study the micromeritic properties, solubility, organoleptic properties, pH, surface tension, viscosity, swelling index and surface characteristics of pectin. Tablets were formulated using pectin and sodium starch glycolate in different concentrations and compared to evaluate disintegrating properties of pectin. Key Findings: Using this new improved technique the yield of extracted pectin was increased and found 25.26%. The result showed that extracted pectin exhibited good flow behavior, micromeritic properties and pH was found 4.15, showed that this can be used in oral formulations without any irritation. Disintegrating properties of pectin was found comparable to sodium starch glycolate and so can be a better substitute for synthetic superdisintegrant. Conclusions: Result showed that this newly developed method can be a technique for waste management of orange fruit based industries. Orange fruit peel derived pectin is a potential candidate to be used as pharmaceutical excipient in solid dosage forms.
Keywords: excipient